Signal integration by DegS and RseB governs the σ(E)-mediated envelope stress response in Escherichia coli - Chaba, Rachna (National Academy of Sciences, 2011)
In Escherichia coli, the σ(E) transcription factor monitors and maintains outer membrane (OM) integrity by activating genes required for assembly of its two key components, outer membrane proteins (OMPs) and lipopolysaccharide (LPS) and by transcribing small RNAs to down-regulate excess unassembled OMPs. σ(E) activity is governed by the rate of degradation of its membrane-spanning anti-σ factor, RseA. Importantly, the DegS protease can initiate RseA cleavage only when activated by binding to unassembled OMPs. The prevalent paradigm has been that the σ(E) response is controlled by the amount of activated DegS. Here we demonstrate that inactivation of a second negative regulator, the periplasmic protein RseB, is also required for σ(E) induction in vivo. Moreover, OMPs, previously known only to activate DegS, also generate a signal to antagonize RseB inhibition. This signal may be lipid related, as RseB is structurally similar to proteins that bind lipids. We propose that the use of an AND gate enables σ(E) to sense and integrate multivariate signals from the envelope.